FFECT OF FENUGREEK SEEDS AND OLIVE LEAVES ON SOME PHYSIOLOGICAL CHARACTERS OF LAYING HEN BREEDERS - Saeb Younis Abdul-Rahman; Ruaa Nathem Shihab Al-Obaidy (Mesopotamia Journal of Agriculture)
This study was conducted on laying hen breeders ( ISA Brown ) to study the effect of Fenugreek seeds and Olive leaves on the physiological performance . 90 hens and 18 cocks (84 weeks age) were divided into 3 groups 16 replicates : 5 hens +1 cock each) , The groups .Were treated daily for 8 weeks as following: 1st group reared on standard ration .2nd reared on standard ration supplemented with crushed Fenugreek seeds (10 gm/kg ration) . 3rd reared on standard ration supplemented with crushed Olive leaves (10 gm/kg ration). Blood samples were collected at the end of 4th week (1st period) and 8thweek (2nd period) . Results revealed that treatment with Fenugreek seeds and Olive leaves improved the physiological performance of layer hen breeders , and showed a significant increase in RBCs ,Hb , PCV % and blood indicis , also treatments caused an improvement in lymphocyte % , clotting time , thrombocytes count, H/L ratio as compared with control . In regard to the sex , the hematological parameters were better in males as compared with females The best results for the interaction effects were recorded in interaction of Fenugreek seeds and Olive leaves treated group at (P ≤ 0.05) .